PENGARUH SIT STRETCHING TERHADAP PERUBAHAN SKALA NYERI PUNGGUNG BAWAH PADA KARYAWAN DI PT. RIFAN FINANCINDO BERJANGKA CABANG SEMARANG - Gamalia Anggriya Dwi Putra; Asti Nuraeni; Mamat Supriyono (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2018)
Lower back pain is one of musculoskeletal disorder in the shape of pain in the back bone, to be exact is in the forth lumbar to the first sacrum. It is caused by the not appropriate posture (not ergonomic) while working or doing the activities, such as very long standing or sitting. This complaint can be reduced by sit stretching regularly. The aim of this study is to find out impact of sit stretching towards the changes of scale of lower back pain on employees at PT. Rifan Financindo Berjangka Branch Semarang. The method of research is quasy experiment designed in pre test and post test with compare group. Research subjects are 30 male and female employees. Sample taking uses total sampling. Statisitic test utilizes Mann Whitney with level of meaning (α=0,05). The result of pre test statisitc test is p-value = 0,467 (> 0,05), it means that there is no significant difference scale of lower back pain between intervention group and compare group before performing sit stretching to intervention group. The post test statisitic the result is p-value = 0,001 (> 0,05), it means there is a significant difference scale of lower back pain at intervention group with compare group after performing sit stretching on the intervention group. Based on result of p-value on post test can be concluded that there is an impact of sit stretching towards the changes in scale of lower back pain on the employees at PT. Rifan Financindo Berjangka Branch Semarang.